(untitled) (IITM Journal of Business Studies, 2024)
The study focuses on examining the impact of quality of services on the satisfaction of customers with samples drawn from NCR. Data related to service quality parameters were collected from 325 respondents using Retail Service Quality Scale (RSQS). Customer satisfaction was measured using four items taken from the scale developed by Bitner and Hubbert (1994). Exploratory factor analysis (EFA) was used to achieve the first objective and Stepwise regression was applied for second objective. During rotation method, 26 items were reduced to five factors and were named after original factors given in the RSQS. EFA revealed that RSQS is partially applicable in Indian retail context and regression results shown that three factors of service quality; PA (Physical Appearance), PI (Personal Interaction) and PS (Problem Solving) have significant contribution to service quality while assessing the customer satisfaction.